Ghana : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
This paper presents the Joint Staff Assessment of the Poverty Reduction Strategy Paper (PRSP) Progress Report for Ghana. IMF staff believes that the Ghana Poverty Reduction Strategy overall provides a sound framework for implementing the government's antipoverty agenda The strategy builds on creating favorable conditions for private-sector-led growth, improving the delivery of basic social services, and raising the efficiency of the public sector. To this end, the government intends to maintain a stable macroeconomic environment with moderate inflation, improve infrastructure and market access, and increase the availability and quality of basic health and education services.